Allochthonous sediment in till near a lithological boundary in central Ontario - Cogley, J.; Aikman, M.; Stokes, D. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1997)
Abstract Clast counts, and measurements of carbonate abundance in the sand fraction, show that little of the till covering a portion of central Ontario was carried across the boundary between Precambrian rocks (up-ice) and Palaeozoic limestone (downice). Seven eighths of the pebble fraction is local, from within ~2-5 km of the site of deposition. The distantly-derived component becomes gradually less abundant down-ice from the lithological boundary, with an exponential distance scale of about 30 km. We ascribe this gradual loss to a combination of comminution and depletion by deposition.However it is not possible to map variations in the abundance of erratics; the pattern is spatially homogeneous and random. The same is true of the abundance of insoluble sand which, moreover, is highly variable.The role of transport of allochthonous sand from the Shield cannot be separated from those of comminution, erosion of local bedrock, postglacial alteration and inheritance of pre-glacial material. The till is best understood as an intimate mixture of "frictional gouge", still more or less in situ , and englacially-transported sediment. Thus it is neither lodgement till nor meltout till; it may be a deformation till, but if so the episode of deformation can have lasted only a few hundred years